Meaning of science communication construct for researchers and public relations at the Indonesian Institute of sciences - Yuriawan, Kapat; Sarwoprasodjo, Sarwititi; Sugiyanto, Dyah Rachmawati (PRofesi Humas, 2022)
Research institutions in Indonesia have an essential role in improving knowledge, skills, and the community’s economy through research results. However, until now, domestic research results have not been well disseminated. One factor that influences it is the not yet optimal collaboration between researchers and public relations as science communicators in communicating research results to the public. They work for a research institution called the Indonesian institute of sciences. This study aims to find out the meaning of science communication for researchers and public relations and how they coordinate these meanings. This study uses a qualitative method with a case study approach. The case study was the dissemination of Beyonic Startmik Biological Organic Fertilizer in Pekalongan, Central Java. The primary data of this study were the results of observations on the conversation between researchers and public relations and semi-structured interviews. The results show that the meaning of science communication for researchers is the activity of conveying scientific information to the public by involving the assistance of public relations and supported by institutional policies. In contrast, the meaning of science communication for Public Relations is the dissemination of scientific information to the public based on information from researchers as a source of information. In coordinating meaning, researchers and public relations discuss the meaning of science communication as a series of communication processes that require the support of researcher competence, public relations communication strategies, and cooperation in building strong relationships with stakeholders.